Niveles de harina de hojas de morera (Morus alba L.) en la alimentacion de pollos broilers. - Tapia Guerra, Mario Eduardo (2009)
In the Area of Poultry Investigation of the UICYT, Fca. "The María" of the UTEQ, located in the km 7 via Quevedo - The Connection, was carried out a titled investigation: " Levels of flour of mulberry leaves (Morus dawn) in diets for chickens broilers"., with a duration of eight weeks, with the following objectives: 1. To determine the best level of inclusion of flour of mulberry leaves (Morus dawn) in diets for chickens broilers in the initial and final stage. 2. To carry out the analysis Benefits Cost of the diets with the help of mulberry leaves (Morus dawn) in diets for chickens broilers in the initial and final stage. 3. To determine if the investigated diets produce some effect in the flavor, color and presentation of the channel of the chickens. 4. To determine the concentration proteínica of the channel of each one of the investigated treatments, by means of chemical analysis. With the purpose of evaluating the relationships in the inclusion of flour of mulberry leaves in the feeding of chickens broilers, on the productive parameters of food consumption (g) gain of weight (g), nutritious conversion, yield to the channel (%), chemical analysis to the channel (breasts) to know him effect of the diets in the concentrations proteicas of the same one, and the profitability of the treatments, 160 chickens were used without sexar and of the line Ross. The treatments were: T1 (0% of mulberry flour), T2 (3% of mulberry flour), T3 (6% of mulberry flour) and T4 (9% of mulberry flour) and T5 (12% of mulberry flour). A design was used totally at random (DCA) with five treatments and four repetitions, The results of this work were subjected to a variance analysis (ANOVA), for the comparisons of stockings of the treatments the test was used from Tukey to 5% of probability. In the food consumption, they didn't register significant differences (P>0.05) among treatments in the phases: initial, final and total; however, numerically the birds fed with the diet witness (Balanced commercial) they reached the biggest consumptions with 494,75 grams and, 1494,32 grams in the two phases. In the variable gain of weight in the initial and total phase did register significant differences among the treatments (P=0.05), I didn't seize, in the final phase. Was it observed that the witness (BC) did he/she obtain bigger earnings of weight in the phases initial and total, with 292,18 g and 748,17 g. In the final phase the T4 did overcome it (9%HHM) with 459,66 g. In the variable nutritious conversion so much in the initial and total phase, could one observe that there were significant differences (P=0.05) among the treatments, finding bigger productive efficiency in the witness (0% Hhm). In the final phase, didn't they register significant differences among the stockings of the treatments, were similar answers obtained however, with the treatments with 9% of Hhm (T4); 6% Hhm (T3) and the witness (0%Hhm). In the Yield to the channel (g/ave) were they statistical differences (P=0.05) in: I weigh I live, I weigh viscera, weight channel, among the treatments. In what refers to weight of fat and yield to the channel there were not significant differences among treatments. The treatment witness was better in weight I live, I weigh to the channel and yield to the channel, with 3500g, 3000 g, and 85,71% respectively. The treatment with 9% of Hhm obtained the smallest quantity in fat in the channel (20 g). Finally, with 6% of Hhm bigger weight of viscera was reached (400 g). In economic terms the treatment with 3, 6 y 9% of flour of mulberry leaves they registered the biggest entrance ($154.79; 154.17 and 153.56), therefore, the net profit ($ 21.23; 22.28 y 23.34), as well as the relationship benefits cost (15.90; 16.89 y 17.92%) they were the best in front of the other treatments in study. Key words: broilers, mulberry, Ross